Sejarah Literasi di Kabupaten Jember Era Klasik dalam tinggalan Arkeologi: Kajian Epigrafi - Ramdhani, Gazza Triatama; Marsyidza, Marsyidza; Sanjoyo, Mawardi Purbo (Local History & Heritage, 2024)
This study explores the development of human literacy based on archaeological evidence found in Jember District, dating back to the classical or medieval period. Using an epigraphic approach, it examines the evolution of language, reading, and writing skills in the region. The analysis focuses on ancient inscriptions engraved on durable surfaces such as stone, metal, pottery, or other resilient materials. These inscriptions often contain significant information about the cultural, religious, political, and social aspects of past societies. The study highlights the patterns of literacy development as an integral part of human culture and civilization, illustrating how early societies documented their knowledge, values, and traditions. The findings reveal that the inscriptions in Jember not only reflect literacy capabilities but also provide valuable insights into societal structures and cultural dynamics during the classical era. It concludes that literacy played a fundamental role in shaping cultural identity and ensuring the preservation of civilization.